Novel of MEMS Resonant Gyroscope using DETF as Sensing Structure - Uvi Desi Fatmawati; Fan Shang Chun; Zhanshe Guo (Proceeding of the Electrical Engineering Computer Science and Informatics, 2014)
Nowadays MEMS product is widely used in all fields such as industry, automation, aerospace, marine, etc. With advances fabrication and lowering cost, MEMS product is very useful and its simple design enabling the user use it easily. This research introduced a new design of MEMS resonant gyroscope using DETF as sensing structure. The decoupled DETF has been designed to be able to produce the natural frequency of 80 KHz, while the whole gyroscope structures generate natural frequency of 3511,8 Hz. Above condition is done to avoid force miss detection in sense mode and drive mode, which has become the biggest problem in gyroscope design. The result showed that the new design of MEMS Resonant Gyroscope is feasible.